2022
DOI: 10.1016/j.therap.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A historical cohort study to investigation of statins safety in COVID-19 hospitalized patients

Abstract: Background and objectives. - A notable proportion of COVID-19 patients need statins for their co-existing conditions. Statins possess several anti-inflammatory properties. We have attempted to describe potential association of exposure to statins and severity of COVID symtpoms in a historical study in hospitalized COVID-19 patients. Methods .- This single-center, historical cohort study was performed in Baharloo hospital as a referral hospital for COVID-19 patients in Tehran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 In 11 studies, ratio measures were close to 1. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 In 2 studies, an increased risk was observed. 58 , 59 Most of these studies were conducted in hospitalized patients and/or patients tested for COVID‐19.…”
mentioning
confidence: 99%
“… 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 In 11 studies, ratio measures were close to 1. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 In 2 studies, an increased risk was observed. 58 , 59 Most of these studies were conducted in hospitalized patients and/or patients tested for COVID‐19.…”
mentioning
confidence: 99%
“…On the other hand, in the present investigation, we found that statin use was associated with an increased risk of ICU admission in our mostly Black cohort. Another study conducted in Tehran found that, on univariate analysis, the use of statins was significantly associated with mortality rate, ICU admission, and length of hospitalization [41]. A study previously conducted at our hospital (Detroit Medical Center) found that statins were associated with reduced mortality in their COVID-19 cohort, consisting of mostly Black individuals, while they found no difference in ICU admission [42].…”
Section: Discussionmentioning
confidence: 83%